The Feminist Declaration Wrapped in Eroticism: A Comparative Study of Female-themed Films - Chen, Guo (Transactions on Social Science, Education and Humanities Research, 2024)
The development of campaign for Equal Rights and related concepts in modern society has indeed captured the interest of feminists regarding gender, body, and identity. Simultaneously, the primary subject matter of traditional eroticism revolves around women, indicating that eroticism offers a comprehensive and distinctive interpretation of these focal points. Within this cultural milieu, the present study examines and interprets the impact of feminism on eroticism, as well as the significant influence of eroticism on the advancement of feminism, by using two films as comparative cases. The films Nymphomaniac Vol. I in 2013 and Poor Thing in 2023 depict distinct female characters in varying manners. The audience can experience a range of emotions through the composition of the shots and the concepts communicated by the two directors. This investigation employs the methodology of feminist literary criticism to study them. The objective of this investigation is to examine the interactions between the female protagonists in these two works, as well as the gender-related themes that are portrayed.